Laboratory and occupation-simulating isokinetic and psychophysical responses of military personnel - James, Jonathan Peter (Rhodes University, Faculty of Science, Department of Human Kinetics and Ergonomics, 2001)
The present study assessed the isokinetic responses of male military personnel(N=42). The study aimed to evaluate the strength capabilities of South African infantrymen and establish benchmark data on a population not previously tested. "Work-simulation" packages have not been widely exploited and this study further aimed to approximate how effectively occupation simulating tasks could identify the capabilities of soldiers. Testing was carried out using a CYBEX 6000 isokinetic dynamometer and involved six laboratory tests (LTs) and four occupation-simulating tests (OSTs). Subjects were required to complete two testing sessions with the order of tests randomized. The LTs consisted of ankle, elbow, hip, knee, shoulder and trunk. In the OSTs, gripping, valve-tightening, wrench-turning and pulling/pushing responses were collected. Slow, medium and fast test speeds were used for each bout. Cardiac responses were measured using heart rate monitoring and perceptual measures assessed using Borg's (1971) RPE scale. The results of the testing showed significant differences in agonist and antagonist responses at all three testing speeds, the only exception being slow speed trunk values (peak torque). Upper- to lower-extremity ratios highlighted a possible weakness in the elbow flexors group, while correlations between LTs and OSTs highlighted the specificity of strength principle, as poor relationships were observed.
Keywords: Isokinetic exercise; Soldiers -- South Africa